THE SOCIAL-PSYCHOLOGICAL AND MEDICAL FACTORS IN THE UPBRINGING OF A CHILD TO BE WELL-ROUNDED AND PHYSICALLY HEALTHY IN THE FAMILY. - Bahronova Mavluda Otkir qizi (KONFERENSIYALAR, 2025)
Abstract: Raising a child to be well-rounded and physically healthy is one of the primary responsibilities of a family. This thesis emphasizes that for this process to be successful, it is essential to consider various social, psychological, and medical factors. The development of a child involves not only acquiring certain knowledge and skills but also the proper formation of their personality, behavior, and health. Only by ensuring this can we raise the children we dream of.